Cooperative GeN Bond Activation in Aluminium‐Functionalised Aminogermanes and Spontaneous Imine Elimination via an Intermediate Germyl Cation. Issue 6 (17th December 2014) - Uhl, Werner; Tannert, Jens; Honacker, Christian; Layh, Marcus; Qu, Zheng‐Wang; Risthaus, Tobias; Grimme, Stefan
Abstract Hydrometallation of iPr2NGe(CMe3)(CCCMe3)2 with HM(CMe3)2 (M=Al, Ga) affords alkenyl–alkynylgermanes in which the Lewis‐acidic metal atoms are not coordinated by the amino N atoms but by the α‐C atoms of the ethynyl groups. These interactions result in a lengthening of the GeC bonds by approximately 10 pm and a comparably strong deviation of the GeCC angle from linearity (154.3(1)°). This unusual behaviour may be caused by steric shielding of the N atoms. Coordination of the metal atoms by the amino groups is observed upon hydrometallation of Et2NGe(C6H5)(CCCMe3)2, bearing a smaller NR2 group. Strong MN interactions lead to a lengthening of the GeN bonds by 10 to 15 pm and a strong deviation of the M atoms from the MC3 plane by 52 and 47 pm, for Al and Ga, respectively. Dual hydrometallation is achieved only with HAl(CMe3)2. In the product, there is a strong AlN bond with converging AlN and GeN distances (208 vs. 200 pm) and an interaction of the second Al atom to the phenyl group. Addition of chloride anions terminates the latter interaction while the activated GeN bond undergoes an unprecedented elimination of EtNC(H)Me at room temperature, leading to a germane with a GeH bond. State‐of‐the‐art DFT calculations reveal that the unique mechanism comprises the transfer of the amino group from Ge to Al to yield an intermediate germyl cation as a strong Lewis acid, which induces β‐hydride elimination, with chloride binding being crucial for providing the thermodynamic driving force.